Study of the tragedy of partition of India and human values depicted in Agyeya’s stories: अज्ञेय की कहानियों में चित्रित भारत-विभाजन की त्रासदी और मानवीय मूल्यों का अध्ययन - Kumar, Rajeshwar (RESEARCH HUB International Multidisciplinary Research Journal, 2023)
Agyeya is a litterateur who addresses the challenges of his time. He is not a creator cut off from his era, rather his sense of the era is full of both breadth and depth. India gets independence in 1947 and the country also faces the tragedy of partition. The tragedy of Partition is not a small incident but there are very few writers who take this subject seriously and create. In fiction, along with Agyeya, Bhishma Sahni, Yashpal, Krishna Sobti, Mohan Rakesh etc. have also written on the tragedy of partition, but in the field of poetry, only Agyeya’s name is notable. It is worth noting that during this period, progressive poets like Baba Nagarjuna, Kedarnath Agarwal, Trilochan, Muktibodh and Shamsher were also creating poetry, but their vision was not on such a big tragedy. Agyeya’s collection titled "Refugees", published in 1948, focuses on the tragedy of the Partition of India. There are a total of eleven poems in this collection titled Refugee, out of which a total of seven poems are written under the title "Parallel Snakes". Apart from this ’Letter Box’, ’Sharanadara’; Muslim -Muslim brother - brother; Badla; and Ramante Tatra Devta – have written these five stories, which underline the beauty of human values even in the tragedy and tragedy of partition.